The Telemedical Literacy and Reproductive Health Literacy in Adolescents in The Urban Area - mubarokah, kismi -; Kurniadi, Arif; Ernawaty, Dyah; Nugraeni, Novita; Nur Fajri, Puput (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2024)
The Maternal Mortality Rate nationally has yet to gain the target of a drop of 183 per 100,000 live births. Telemedical literacy is an innovation to improve access to information and health services, including youth reproductive health. The study aims to analyze the correlation between telemedical literacy and reproductive health literacy in adolescents in the Middle Semarang Subdistrict. This observational study uses a cross-sectional design. The data from 200 teenagers were collected through a self-administered online questionnaire and analyzed using a rank spearman test. The results showed that telemedical and reproductive health literacy were sufficient. Age and education correlate positively to both telemedical literacy and reproductive health literacy. Telemedical literacy also associates with reproductive health literacy (p0.001). Government and private health institutions must increase reproductive health campaigns through online media.